Cassava as an insurance crop in a changing climate: The changing role and potential applications of cassava for smallholder farmers in Northeastern Thailand - Polthanee, Anan (Forest and Society, 2018)
Approximately 80 percent of the 22 million people in Northeastern Thailand are engaged in agriculture, and the per capita income of the region is lower than in any other part of Thailand. The major constraint to crop production is rainfall. Although the region has an average annual rainfall greater than 1200 mm, the seasonal distribution of rainfall makes for challenging agricultural cultivation opportunities. The climate is characterized by rainy (May-October) and dry (November-April) seasons. Most (90%) farming is cultivated under rainfed conditions. In addition, most soils are characterized by a sandy texture, high acidity, low organic matter, low level of plant nutrients and low water holding capacity. Due to these conditions, and an increasingly unpredictable climate horizon, cassava has come to play an important economic role for smallholder farmers in the region. The inherent tolerance of cassava to stressful environments, requires minimal care, less investment, and provides greater flexibility in planting and harvesting. Although cassava is grown as a monoculture crop, it can also be grown profitably as a second crop in rice-based cropping systems without supplemental irrigation during the dry season, as well as intercropped in rubber plantations at early growth stages. Given the importance of cassava in farmer income, export values, marketing, and labor, this paper discusses the broader socio-economic and biophysical aspects of cassava due to its important role in future agrarian change for the region.